2011
DOI: 10.1111/j.1745-3933.2011.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

A third H i 21-cm absorption system in the sight-line of MG J0414+0534: a redshift for Object X?

Abstract: We report the detection of the third H i 21‐cm absorber in the sight‐line towards the z= 2.64 quasar MG J0414+0534 (4C +05.19). In addition to the absorption at the host redshift and in the z= 0.96 gravitational lens, we find, through a decimetre‐wave spectral scan towards this source, strong absorption at z= 0.38. We believe this may be associated with ‘Object X’, an additional feature apparent in the field of the lensing galaxy and lensed images, on the basis of its close proximity to the quasar images and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…However, despite four decades of searches, knowledge of the cool component of this gas in the distant (z > ∼ 0.1) Universe remains very scarce, with only 42 cases reported in these absorbers, intervening radio-loud QSOs (quasars) 1 , in addition to 35 associated with the quasar host galaxy itself. 2 sjc@physics.usyd.edu.au 1 Compiled in Curran (2010), with the addition of those recently reported by Srianand et al (2010); Curran et al (2011c).…”
Section: Introductionmentioning
confidence: 73%
“…However, despite four decades of searches, knowledge of the cool component of this gas in the distant (z > ∼ 0.1) Universe remains very scarce, with only 42 cases reported in these absorbers, intervening radio-loud QSOs (quasars) 1 , in addition to 35 associated with the quasar host galaxy itself. 2 sjc@physics.usyd.edu.au 1 Compiled in Curran (2010), with the addition of those recently reported by Srianand et al (2010); Curran et al (2011c).…”
Section: Introductionmentioning
confidence: 73%
“…No published spectroscopy exists of neighbouring field galaxies, although Tonry & Kochanek (1999) presented long-slit spectroscopy of the lensing galaxy, taken with the slit placed across "Object X", the closest field galaxy. Curran et al (2011c) identified two peaks in the low-resolution spectrum at the wavelengths expected for [O iii] at z=0.3789. It is likely, then, that this object does not correspond to either of the detections presented here.…”
Section: Optical Counterpartsmentioning
confidence: 91%
“…We have now completed the analysis of the data along the entire redshift space towards MG J0414+0534 (see Curran et al 2011c for details), upon which we find a further two possible absorption profiles, near 926 MHz and 1061 MHz. The absorption feature close to 926 MHz was the least subject to radio frequency interference (RFI), which appears as narrow lines and amplitude fluctuations.…”
Section: The Detection Of One (And Possibly Two) New Absorption Featu...mentioning
confidence: 99%
“…An alternative target for molecular absorption is towards the fainter ‘red quasars’, where the red colour may indicate an intervening column of dust. However, due to the relatively narrow bandwidths in the millimetre band (see ), such an approach is currently only practical at longer (decimetre) wavelengths (see Curran et al 2011b). In the absence of any known intervening absorbers, selecting the quasar itself gives a redshift ( z em ) to which to tune the receiver.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the relatively narrow bandwidths in the millimetre band (see Sect. 4.2), such an approach is currently only practical at longer (decimetre) wavelengths (see Curran et al 2011b). In the absence of any known intervening absorbers, selecting the quasar itself gives a redshift (zem) to which to tune the receiver.…”
Section: Introductionmentioning
confidence: 99%